Urban Slum Residential Areas: Policy Model for Domestic Wastewater Management (Case Study: Maleer Sub-district, Bandung City) - Ken Aryu Ruska Yuniar; Ahmad Soleh Setiyawan (Jurnal Serambi Engineering, 2024)
One of Bandung's residential slum areas, the Maleer sub-district, has been identified as a priority sanitation area, particularly in terms of wastewater management. In order to improve wastewater management in the slum area, technical and non-technical aspects are considered. This study aims to know the wastewater management policy factors that affect the sustainability of the wastewater management system and to propose a policy model in the slum area. A convenience sampling method was used to collect data from 99 respondents and 7 institutional respondents using a self-administered questionnaire. Partial least square structural equation modelling (PLS-SEM) was used to test the proposed model. The sanitation risk index value in a slum area of Maleer district was 283. Some factors affecting the sustainability of sanitation system arranged by value correlation were (0.325) for technical aspects, (0.283) for community participation, (0.272) for management institution and (0.174) for financial aspect, respectively. The existing policy model only included technical and financial factors, while community participation and management institution were not included in the existing policy. In developing a new model of slum sanitation to achieve sustainability, factors in the form of active community participation and presence of management institution need to be added.